Efektivitas Metode RICE pada Sprain Ankle Akut Pemain Sepak Bola: Pendekatan Retrospektif - Liwaulhamdiah, Nur Aulia (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2025)
This study aims to evaluate the effectiveness of the RICE method (Rest, Ice, Compression, Elevation) in healing acute ankle sprains in KONI Makassar City soccer players. The study used a non-experimental quantitative approach with a retrospective observational design. The sample consisted of 34 players selected using purposive sampling and instruments in the form of a 4-point Likert scale questionnaire to measure the application of the RICE method and the level of injury recovery. Data analysis was performed through validity, reliability, normality, multicollinearity, heteroscedasticity, and Spearman's rho correlation tests. Furthermore, the relationship between variables was analyzed using simple linear regression. The results showed a significant effect between the RICE method and the healing process of acute ankle sprains (p-value = 0.000 < 0.05). A correlation coefficient value of 0.603 indicates a fairly strong positive relationship, while a coefficient of determination (R²) value of 0.395 shows that the RICE method contributes 39.5% to injury healing. Thus, the RICE method has been proven effective in assisting the healing process of acute ankle sprains, although its effectiveness is still limited, requiring additional approaches for more optimal recovery results.